(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
Traditional portfolio optimization strategies face significant challenges in fragile financial markets due to the scarcity of reliable data and acute sectoral concentration. This study aims to evaluate the effectiveness of the naive diversification strategy (1/N rule) in reducing portfolio risk within a fragile market environment, represented by the Damascus Securities Exchange, which suffers from banking sector dominance exceeding 70% of its market capitalization. Using a bootstrap simulation methodology and Monte Carlo simulation to generate thousands of investment portfolios, and analyzing the evolution of risk measures (standard deviation, coefficient of variation, Value at Risk - VaR, and Conditional Value at Risk - CVaR) as the number of stocks increases, the results show that naive diversification is effective in reducing risk in the initial stages, with the majority of risk reduction achieved when adding 15-20 stocks. However, the marginal benefits of diversification dissipate after reaching a threshold ranging between 22 and 24 stocks, where adding more stocks does not lead to a statistically significant reduction in risk measures. The study finds evidence of "diversification traps" in fragile markets and recommends that investors focus on the quality of diversification rather than merely increasing the number of assets, and avoid exceeding 23 stocks in their investment portfolios in the Damascus Securities Exchange.